2019
DOI: 10.1038/s41598-019-50377-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective activation of astrocytes by methylmercury exposure in the inferior colliculus

Abstract: Methylmercury (MeHg) is well known to induce auditory disorders such as dysarthria. When we performed a global analysis on the brains of mice exposed to MeHg by magnetic resonance imaging, an increase in the T1 signal in the inferior colliculus (IC), which is localized in the auditory pathway, was observed. Therefore, the purpose of this study is to examine the pathophysiology and auditory dysfunction induced by MeHg, focusing on the IC. Measurement of the auditory brainstem response revealed increases in late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Furthermore, rats acutely exposed to Methyl-Hg via oral administration, were found to undergo an increase of BDNF levels, which was linked to alteration of gut-brain axis related metabolites [ 80 ]. Increased expression of BDNF was found in astrocytes of the inferior colliculus (a brain region involved in auditory control) in Methyl-Hg-exposed mice [ 81 ]. Increased BDNF levels were also found in the cerebellum of adult male mice exposed for 2 weeks to 40 μg/mL Methyl-Hg (diluted in drinking water, ad libitum ), which also showed motor impairments characteristic of cerebellar toxicity [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rats acutely exposed to Methyl-Hg via oral administration, were found to undergo an increase of BDNF levels, which was linked to alteration of gut-brain axis related metabolites [ 80 ]. Increased expression of BDNF was found in astrocytes of the inferior colliculus (a brain region involved in auditory control) in Methyl-Hg-exposed mice [ 81 ]. Increased BDNF levels were also found in the cerebellum of adult male mice exposed for 2 weeks to 40 μg/mL Methyl-Hg (diluted in drinking water, ad libitum ), which also showed motor impairments characteristic of cerebellar toxicity [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that methylmercury-induced interleukin-6 (IL-6) expression in astrocytes suppresses methylmercury-induced neuronal cell death 15 , 16 . Induction of methylmercury-induced IL-6 expression in the astrocytes in the midbrain of mice has been shown to be protective against methylmercury-induced hearing impairment 17 . Furthermore, we found that methylmercury-induced expression of the chemokine CCL4 in the mouse brain suppresses neuronal damage 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Astrocytes, the most abundant cell type in the CNS, are functionally and structurally associated with numerous pathological responses to disease ( 32 ). It has also been reported that astrocytes aggravated ischemic stroke injury; however, they also exert neuroprotective effects by releasing neurotrophic proteins ( 33 , 34 ). At present, certain astrocyte-based neuroprotective treatment strategies include treatment for astrocyte protection ( 35 ), astrocyte anti-excitotoxicity and antioxidation ( 36 ), as well as astrocyte-derived growth factors ( 37 ).…”
Section: Discussionmentioning
confidence: 99%